Developing a Supply Chain Subsystem to Manage the Process of Obstacle Elimination for the Innovative Development of Business Entities - Alexey A. Kuzubov; Nina V. Shashlo; Galina V. Petruk; Aleksandr A. Korostelev (International Journal of Supply Chain Management, 2018)
Abstract- The negative trend protests in economic development reflect the lack of a systematic approach to innovative development and innovative process management. An important feature of innovative development is to ensure the elimination of obstacles to innovative development, to avoid threats and crisis situations in the activities of business entities. Thus, one of the urgent problems is the prediction of crisis phenomena, events, situations, the search for their elimination or leveling trends, the formation of preventive measures for their prevention and overcoming, the increase of strategic management effectiveness by innovation development in general. The purpose of the article is to develop a supply chain subsystem to manage the process of obstacle elimination for the innovative development of business entities. In order to achieve this goal, the following research methods were used: analysis and synthesis, schematic and graphic representation, modeling and forecasting, formal-logical method. The goal, the properties and the structure of process management supply chain subsystem to eliminate the obstacles to innovative development were substantiated. It was proved that the innovation strategy of economic entities should be subjected to certain adjustments in accordance with the dynamic changes in environmental conditions and the features of business entity functioning in it. They developed the model of innovative development process for an entrepreneurial entity using the removal of obstacles to innovative development, based on creativity, leadership competence, the delegation of managerial powers, the coordination of activities and cooperation. The main characteristics and the obstacles of each stage of the model are substantiated in order to develop appropriate programs and activities for their overcoming. The scientific novelty of the research is the development of the classification set of phenomena, events and situations. These elements create the obstacles to the innovative development of business entities, as well as the ways to overcome the obstacles that threaten innovative development, which contributes to the improvement of the decision-making process in the field of an innovative strategy development for business entities. Keywords: innovative development, supply chain management subsystem, obstacle elimination, business entities, strategic management